2008
DOI: 10.1210/jc.2008-0379
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Hormones and Skeletal Health in Young Women

Abstract: I n young women, low estrogen levels complicate a wide variety of diseases, including premature ovarian failure, anorexia nervosa, athletic amenorrhea, prolactinoma, hypopituitarism, and chronic kidney disease. Hypoestrogenemia may also result from therapy with GnRH agonists, glucocorticosteroids, chemotherapy, and especially aromatase inhibitors. All of these situations are associated with bone loss, because estrogen chronically suppresses bone resorption. Several mechanisms are involved: 1) estrogen increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This is consistent with the results of Scholl et al, who reported that higher concentrations of leptin during the third trimester of pregnancy were correlated with a greater increase in knee height [9]. In contrast, high estradiol concentrations were associated with a lower increase in height [46]. Our univariate linear model did not show differences in height increase between those who breastfed and those who did not.…”
Section: Bone Age Stature and Leptin Igf-i And Estradiol Levelssupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the results of Scholl et al, who reported that higher concentrations of leptin during the third trimester of pregnancy were correlated with a greater increase in knee height [9]. In contrast, high estradiol concentrations were associated with a lower increase in height [46]. Our univariate linear model did not show differences in height increase between those who breastfed and those who did not.…”
Section: Bone Age Stature and Leptin Igf-i And Estradiol Levelssupporting
confidence: 92%
“…As demonstrated in our study, pregnant adolescents could still grow, but probably to a lesser degree. Growth plates close approximately a decade after a teenager reaches her maximum height, meaning that a pregnant adolescent could still have time to grow [46]. We believe that this was the case in our participants, especially those who showed high concentrations of leptin.…”
Section: Bone Age Stature and Leptin Igf-i And Estradiol Levelsmentioning
confidence: 71%
“…These studies report conflicting results ( Bancroft et al ., 1991b ; Schaffir, 2006 ; Graham et al ., 2007 ; Greco et al ., 2007 ; Strufaldi et al ., 2010 ; Caruso et al ., 2011 ; Battaglia et al ., 2012 ; Elaut et al ., 2012 ; Pastor et al ., 2013 ). Although estrogens have been clearly identified as key hormones for maintaining bone mass ( Ott et al ., 2001 ; Riggs et al , 2002 ; Ott, 2008 ), androgens are also important regulators of skeletal growth and maturation ( Martel et al ., 1998 ; Riggs et al , 2002 ; Hartard et al ., 2006 ). Data on the effect of androgens in women are scarce but T may exert an effect on protein synthesis and increase muscle mass ( Gower and Nyman, 2000 ; Ružić et al ., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens also stimulate bone formation by reducing apoptosis of osteoblast cell lines and increasing the secretion of transforming growth factor-beta, bone morphogenetic proteins, and insulin-like growth factor-1. 10,11 Conversely, estrogen deprivation after chemotherapy-induced ovarian atrophy leads to a wave of new remodeling sites by upregulation of T cells, osteoblasts, and stromal cells to produce a surge of cytokines such as interleukin-1, interleukin-6, tumor necrosis factoralpha, and RANK-L, all of which leads to enhanced osteoclast activity, the net effect of which is to tip the balance of bone turnover towards resorption. Declining estrogen stimulation in the osteoblast seems to induce estrogen receptor-alpha binding to transcriptional enhancers of Fas-ligand which upregulate the Fas-ligand gene, apparently increasing osteoclast apoptosis through a paracrine mechanism.…”
mentioning
confidence: 99%